Impacts of design-based professional development on teacher educators’ integration of Google apps into course instruction - Shibru Seboka; Joseph Nehru; Tariku Sime (Discover Education)
Abstract This study investigated the impacts of a design-based professional development (DBPD) training program on English language teacher educators’ (ELTEs’) integration of Google Apps into course instruction at Jimma College of Teacher Education, Ethiopia. Using a mixed-method case study design, the study examined ELTEs’ pre-training digital literacy gaps, post-training improvements of both ELTEs and English language teacher candidates (ELTCs) and challenges encountered during implementation. Nine ELTEs and a class of third-year ELTCs were purposefully selected, and data were gathered through questionnaires, interviews, observations, and focus group discussions administered to the TEs. Findings from the pre-training phase revealed limited digital literacy and confidence among ELTEs, coupled with minimal prior exposure to targeted educational technologies. In the post-training, however, ELTEs demonstrated substantial improvements in technological proficiency, confidence, and adoption of diverse, student-centred teaching approaches. This improvement aligns with increased engagement and motivation observed among TCs, who gradually adapted to using Google Apps despite initial technical and infrastructure barriers. Nevertheless, implementation challenges persisted, including inadequate technology infrastructure, pedagogical alignment issues, and limited institutional support. These findings implicated the potential of structured, hands-on professional development programs like DBPD in promoting technology adoption among educators, though addressing contextual barriers remains critical for broader success. Despite its contributions, the study's findings were limited by the lack of a rich technological environment and participants’ characteristics and prior awareness which may affect generalizability and long-term implications.